2018
DOI: 10.3390/nu10010082
|View full text |Cite
|
Sign up to set email alerts
|

Rational Management of Iron-Deficiency Anaemia in Inflammatory Bowel Disease

Abstract: Anaemia is the most frequent, though often neglected, comorbidity of inflammatory bowel disease (IBD). Here we want to briefly present (1) the burden of anaemia in IBD, (2) its pathophysiology, which mostly arises from bleeding-associated iron deficiency, followed by (3) diagnostic evaluation of anaemia, (4) a balanced overview of the different modes of iron replacement therapy, (5) evidence for their therapeutic efficacy and subsequently, (6) an updated recommendation for the practical management of anaemia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 203 publications
(323 reference statements)
1
64
0
4
Order By: Relevance
“…The latest ECCO guidelines on the management of IDA in IBD recommend IV iron as first-line treatment, due to its safety, efficacy, good tolerability, and fast response [22,27,39]. Although oral iron may be an option for mild anemia, it is less effective than IV iron, due to IBD-associated malabsorption [23-25, 28, 29], and requires prolonged administration (minimum 3 months), being often associated with gastrointestinal intolerance [31][32][33].…”
Section: Which Methods Of Iron Supplementation To Usementioning
confidence: 99%
See 1 more Smart Citation
“…The latest ECCO guidelines on the management of IDA in IBD recommend IV iron as first-line treatment, due to its safety, efficacy, good tolerability, and fast response [22,27,39]. Although oral iron may be an option for mild anemia, it is less effective than IV iron, due to IBD-associated malabsorption [23-25, 28, 29], and requires prolonged administration (minimum 3 months), being often associated with gastrointestinal intolerance [31][32][33].…”
Section: Which Methods Of Iron Supplementation To Usementioning
confidence: 99%
“…Over the last decade, new IV iron formulations have emerged with a more favorable efficacy and safety profile, including iron sucrose and ferric carboxymaltose [30][31][32]. A recent review suggested that oral iron should be preferred for patients with quiescent IBD disease and mild IDA, while IV iron supplementation should be the best option for patients with active IBD and for those with inadequate response to or DOI: 10.1159/000505071 side effects with oral formulations [33]. In pediatric patients, evidence is still lacking, with no diagnostic or therapeutic guidelines specifically focusing on this age group.…”
Section: Introductionmentioning
confidence: 99%
“…У літературі обговорюється питання необхідності раннього початку терапії при залі зодефіцитних станах (уже на етапі латентного дефіциту заліза) у дітей із важкою патологією кишечника [1,10]. Проте чинна практика лікування запальних захворювань кишечника у дітей характеризується тим, що лікарі в багатьох випадках приділяють недостатньо уваги проблемі анемії, вважаючи, що терапія ентеральними препаратами заліза може погір шити перебіг основного захворювання, не враховуючи негативний вплив анемії на якість життя дитини та її подальший розвиток [7,9].…”
Section: вступunclassified
“…Як свідчать результати клінічних спостережень, одним із найчастіших ускладнень ентероколіту у дітей є анемія. За даними різних авторів, вона спо стерігається у 6-74% дітей із запальними за хворюваннями кишечника (здебільшого цей показник становить 35-60%) [7,11]. Найвищою є частота анемії серед пацієнтів раннього віку [1,4].…”
Section: вступunclassified
See 1 more Smart Citation